Identifying Blood-Based Protein Biomarkers for Antiangiogenic Agents in the Clinic. Issue 4 (July 2015) - Hatch, Ace J.; Clarke, Jeffrey M.; Nixon, Andrew B.; Hurwitz, Herbert I.
<x xml:space="preserve">Abstract</x> Abstract Agents that inhibit tumor angiogenesis are widely used and have provided meaningful survival benefits to patients in multiple disease settings. However, these agents differ significantly in their mechanisms of action and potential toxicities, and there are currently no prospectively validated biomarkers to guide the selection of agents for individual patients. Blood-based protein biomarkers are well suited for trials investigating antiangiogenic agents for multiple reasons. Many elements of the molecular pathways that antiangiogenic agents target are present and detectable in the circulation, sample collection is minimally invasive, and samples can be collected throughout the course of treatment. Blood-based biomarkers for antiangiogenic therapies are urgently needed to guide the development of therapeutic strategies. This review provides a brief summary of the current blood-based protein biomarkers for antiangiogenic therapies.